Inkompatibilitas Asas Pengaturan Sistem Pemilu dengan Sistem Pemerintahan Presidensial di Indonesia - Agus Riwanto (Jurnal Hukum IUS QUIA IUSTUM, 2014)
This study examines, first, whether the principles contained in the Electoral Act Norms are incompatible with the presidential system of government? Second, what is the cause of the incompatibility between the electoral system and the presidential system? Third, what are its influences in the practice of the implementation of presidential system of government which is based on the 1945 post-amendment? This study uses normative legal research (doctrinal) focusing on literature data. The study concluded that, first, the principles of the electoral system and the presidential system of government did not support each other as one integrated system. Second, the cause of incompatibility between these two systems was because the norms and provisions in the legislation governing the electoral systems of its principles were incompatible with the principles of presidential system of government. Third, the effect was not able to support the effectiveness of the course of the practice of the organization of presidential system of government which is based on the 1945 post-amendment.